Stronger together: advancing equity in global health research partnerships - Ingenhoff, Rebecca; Sarker, Malabika; Hanson, Kara; Rashid, Sabina Faiz; De Allegri, Manuela; Jones, Ffion Storer; Cook-Deegan, Maeve; Anton, Nora; Sewankambo, Nelson K. (BMJ global health, 2025)
Achieving genuine equity in global health research partnerships remains a critical challenge, as persistent asymmetrical dynamics between researchers from high-income countries (HICs) and low- and middle-income countries (LMICs) hinder collaboration and impact. These dynamics manifest in funding imbalances, inadequate LMIC-led research support, inequitable benefit distribution and systemic barriers hindering scientific progress. - Convened by the German Alliance for Global Health Research (GLOHRA), the recent World Health Summit 2024 offered the opportunity to bring together experts from academia, government and civil society to discuss the need to shift global health research partnerships from extractive to truly collaborative models. Participants, from both LMICs and HICs, openly discussed critical challenges like funding inequities and biases and disparities in credit and decision-making between HIC and LMIC researchers. - Key strategies presented included rethinking funding structures, strengthening local research capacity, prioritising LMIC-driven agendas, ensuring fair recognition and establishing truly equitable policies. Building on the conversations held at the World Health Summit, the following actionable steps contribute to the growing discourse on fostering equitable practices in global health research. Given the current shifts in global political priorities and funding landscapes, it remains important to sustain attention on equity in research partnerships. This commentary seeks to reflect ongoing challenges and offer practical considerations for advancing equitable collaborations.
Online erschienen: 23. Juni 2025
Gesehen am 12.01.2026